Bonjour merci de m'aider
A=(-6)+(+8)=
B=(-5)+(-3)=
C=(-7,4)+(+2,8)=
D=(-6)-(-3)=
E=(-7)-(+4)=
F= -2-5=
G= -9+6=
H= -5+4+8-5-8=

1
A=(-6)+(+8)=2
A= 2
B= -8 ( car - et - est égal à - mais on ajoute les résultats)
C= -4.7
B=(-5)+(-3)=-8
C=(-7,4)+(+2,8)=-4,6
D=(-6)-(-3)=-3
E=(-7)-(+4)=-11
F= -2-5=-7
G= -9+6=-3
H= -5+4+8-5-8= -6

Réponses

2013-10-13T15:45:03+02:00
A = (-6) + (+8) = 2
B = (-5) + (-3) = -8
C = (-7,4) + (+2,8) = -4,6
D = (-6) - (-3) = -3
E = (-7) - (+4) = -11
F = -2 - 5 = -7
G = -9 + 6 = -3
H = -5 + 4 + 8 - 5 - 8 = -1 + 3 - 8 = 2 - 8 = -6